Phytocompounds of Anonna muricata leaves extract and cytotoxic effects on breast cancer cells - Rahman, Husna Syakirah Ab; Ibrahim, Wan Suriyani Wan; Ismail, Norzila; Ismail, Tuan Nadrah Naim Tuan; Salleh, Siti Farhanah Mohd; Pak, Michael Kai Wong; Samad, Mohd Ridzuan Abdul; Hashim, Mohd Nizam Md (Hainan Medical University, Institute of Tropical Disease, 2018)
Objective: To identify the phytochemical compounds from Annona muricata (A. muricata) and to determine their in vitro anti-proliferative activities against breast cancer cells, MCF7 and MDA-MB-231. Methods: A. muricata leaves were successively extracted by soxhlet method using n-hexane, ethyl acetate and methanol, and decocted with water. Each extract was analysed by gas chromatography mass spectrometry (GCMS) and characterized with Wiley and NIST library searches. Anti-proliferative activity of each extract was evaluated on MCF7 and MDA-MB-231 breast cancer cells using MTT assay. Results: The GCMS analysis of different solvent extracts of A. muricata leaves showed presence of different chemical groups of compounds such as steroids, terpenoids, phenolic compounds, sugars, sugars alcohol and others including vitamin E. Ethyl acetate leaves extract exhibited the lowest IC50 value on the MDA-MB-231 breast cancer cell and n-hexane leaves extract showed the the lowest IC50 value on the MCF-7 breast cancer cell. Conclusion: Steroids and phenolic compounds were the main phytocompound groups identified from all A. muricata leaves extracts. The antiproliferative activity of n-hexane and ethyl acetate extract towards breast cancer MCF7 and MDA-MB-231 respectively might be due to the presence of biologically active compounds in the extracts, hence, providing some scientific evidences of the effectiveness of its traditional usages.